The 2022 ParticipACTION Report Card on Physical Activity for Children and Youth: Focus on the COVID-19 pandemic impact and equity-deserving groups - Kuzik, Nicholas; Cameron, Christine; Carson, Valerie; Chaput, Jean-Philippe; Colley, Rachel; Doiron, Joe; Faulkner, Guy; Janssen, Ian; Saunders, Travis; Spence, John C.; Tucker, Patricia; Vanderloo, Leigh M.; et al. (Frontiers in Public Health, 2023)
Introduction: The ParticipACTION Report Card on Physical Activity for Children and Youth is the most comprehensive national assessment of physical activity and related behaviours, characteristics, and opportunities for children and youth. The 2022 Report Card assigned grades based on data gathered during the COVID-19 pandemic to reflect this extraordinary time-period in Canada. Further, while not graded, efforts were made to summarize key findings for early years children and those identifying as: having a disability, Indigenous, 2SLGBTQ+, newcomers to Canada, racialized, or girls. The purpose of this paper is to summarize the 2022 ParticipACTION Report Card on Physical Activity for Children and Youth. Methods: The best available physical activity data captured during the COVID-19 pandemic was synthesized across 14 different indicators in four categories. The 2022 Report Card Research Committee assigned letter grades (i.e., A-F) based on expert consensus of the evidence. Synthesis: Grades were assigned for: Daily Behaviours (Overall Physical Activity: D; Active Play: D-; Active Transportation: C-; Organized Sport: C+; Physical Education: Incomplete [INC]; Sedentary Behaviours: F; Sleep: B; 24-Hour Movement Behaviours: F), Individual Characteristics (Physical Literacy: INC; Physical Fitness: INC), Spaces & Places (Household: C, School: B-, Community & Environment: B), and Strategies & Investments (Government: B-). Compared to the 2020 Report Card, the COVID-19 specific grades increased for Active Play and Active Transportation; and decreased for Overall Physical Activity, Sedentary Behaviours, Organized Sport, and Community & Environment. There were many data gaps for equity-deserving groups. Conclusion: During the COVID-19 pandemic, the grade for Overall Physical Activity decreased from a D+ (2020) to a D, coinciding with decreases in grades reflecting fewer opportunities for sport and community/facility-based activities as well as higher levels of sedentary behaviours. Fortunately, improvements in Active Transportation and Active Play during COVID-19 prevented a worse shift in children’s health behaviours. Efforts are needed to improve physical activity for children and youth during and post-pandemic, with a greater emphasis on equity-deserving groups.